The Role of KKN Students in the Development of Sustainable Tourism Villages - Lisi, Fitra Hataya; Maulia, Winda; Rahmawati, Baiq Ovi; Rahmadiani, Sukma; Fatmawati, Nurul; Nisa, Zia Muazzatun; Safii, Muhammad; Erlangga, Ithnan Baqi Putra; Miftahurrizki, Miftahurrizki; Rizqon, Lalu Khairil; Saipudin, Lalu (Unram Journal of Community Service, 2024)
Desa Lenek Ramban Biak has transformed into an ecotourism village due to its various tourism potentials, including natural, cultural, and religious attractions. However, both the government and local communities lack awareness of the importance of managing village tourism. Through the Community Service Program (Kuliah Kerja Nyata) conducted by PMD UNRAM, efforts have been made to enhance cleanliness and attract more visitors. Activities include creating photo spots, producing promotional videos, and establishing waste disposal facilities through collective clean-up efforts. The implementation methods involve crafting waste bins from recycled bamboo, conducting clean-up drives at tourist spots, producing promotional videos, and creating photo spots using wood and bamboo. The addition of photo spots aims to make the tourist destination more appealing. The use of bamboo waste bins is intended to raise awareness among the community about waste management and promote a cleaner and healthier environment. Additionally, leveraging technological advancements for promotional video production facilitates wider outreach through social media platforms, thereby increasing awareness among the public. Social media serves as a convenient channel for disseminating information about the tourist destination.